A combination of morphological and molecular analyses to distinguish two fungal pathogens causing leaf spots on Cinnamomum burmannii. Issue 5 (15th April 2014) - Yuelian, L.; Fengqiu, X.; Woodward, S.
Summary The leaves of Cinnamomum burmannii in Guangdong Province were severely affected by two distinctly different types of spots. The dark spot was round, surrounded by a thin yellow zone at the interface between healthy and affected regions, and had a distinct dark ring. The yellow spot had an irregular shape and a broad yellow halo. The pathogens from the different diseased leaves were isolated and were shown to be of two different strains, both of which caused leaf spot disease in pathogenicity tests. Based on the morphological characteristics and ITS sequence, the strain causing the dark leaf spot was identified as Phyllosticta cirsii, and that causing the yellow leaf spot as Phomopsis cinnamomicola Z.D. Jiang et al. This paper is the first to report two pathogens causing leaf spots on Cinnamomum burmannii.